Phytochemistry and fungitoxic potential of extract and fractions of Pouteria ramiflora on Fusarium solani f. sp. phaseoli (Bioscience Journal, 2019)
Among the fungus that attack the common bean crop there is Fusarium solani f.sp. phaseoli (Fsp), causing major losses. Taking into account its importance, the objective of this work was to determine the secondary metabolites class and the potential fungicide of the Pouteria ramiflora leaves on Fsp. The ethanol extract was dissolved in methanol/water and partitioned successively with hexane, dichloromethane, chloroform, ethyl acetate and butanol, subjected to the chemical profile. The solutions were prepared in concentrations of 800, 1200, 1600, 2000 and 2400 µg/mL and poured into Petri dishes; then, 0.5 cm disc of diameter with spores and mycelia of Fsp was deposited. These dishes were incubated in temperature of 25 ± 2 °C and the evaluations, performed by measuring the colonies diameter (five replications) until reaching the dishes border (three days) with a completely randomized experimental design. Through the Mycelial Index Growth Speed (MIGS) data, analysis of variance was performed and when significant, applied the regression analysis. The results indicated that all fractions and the extract have the phenolic compounds and/or derivatives as one of the major constituents except the hydroethanolic fraction. The extract and its fractions decreased the Fsp MIGS, in the same proportion in which concentrations were increased; the greatest reduction occurred in the butanol fraction at the concentration of 2400 μg/mL, with growth close to zero, indicating its potential use for the Fsp control, probably due to the presence of anthraquinones.